Policy inconsistency detection bassed on RBAC model in cross-organizational collaboration - Poh, Kuang Teo; Ibrahim, Hamidah; Sidi, Fatimah; udzir, Nur Izura (2011)
Policy integration and conflict resolutions among various organizations still remain a major challenge.Moreover, policy inconsistency detection approach with logical reasoning techniques which considers integration requirements from collaboration parties has not been well studied.In this paper, we proposed a model to detect inconsistencies based on role-based access control (RBAC) that considers role hierarchy (RH) and temporal and spatial constraints.A model to prune and collect only the required policies based on access control requirements from different organizations is designed.Policy inconsistency detection should be enhanced with logical-based analysis in order to develop security policy integration.We believe this work could provide manner to filter a large amount of unrelated policies and only return potential collaboration policies for conflict resolution.